Phrases Used in Medical Communication, Their Timing and Frequency - Placencia Ibadango, Martha Veronica (2024)
Introduction: The duration of the consultation was a matter of restlessness, as well as communication, which seems to be an indicator in almost each of the activities of the medical-patient interview. Objetive: Interpret the terms and phrases in the medical consultation in a hospital in the town and evaluate the era and communication between the doctor and the patient. Method: The detailed and observer transverse study carried out in 3 stages: stage 1 observation and selection of the terms achieved in the doctor-patient consultation; Registration of stage 2 of the terms by frequency, their use and the time dedicated to the medical consultation; Stage 3 Equivalence selection in English using bibliographic translators. Conclusions: Doctors and patients have rights and obligations to be respected based on a sociological and ethical aspect, therefore, the consultation of professional health practice should take into account the era and opinions of patients, as well as the doctor to contemplate the dignity of the experts. attention. Results: 78 terms or phrases were identified in the medical consultation; 59 came from patients and 19 doctors, often in gynecology and medical consultation of internal medicine. The average time in each consultation has been 20 minutes.